Abnormal plasma ceramides refine high-risk patients with worsening heart failure - Ren, Lu; Li, Fengjuan; Tan, Xin; Fan, Yangkai; Ke, Bingbing; Zhang, Yixin; Jiang, Hongfeng; Jia, Lixin; Wang, Yuan; Du, Jie (Frontiers in Cardiovascular Medicine, 2023)
Worsening heart failure (WHF) is a heterogeneous clinical syndrome with a poor prognosis. Therefore, more effective risk stratification tools are required to identify high-risk patients. Evidence suggests that aberrant ceramide accumulation can be affected by heart failure risk factors and is a driver of tissue damage. We hypothesized that specific ceramide lengths and ratios could serve as biomarkers for risk stratification in patients with WHF by reflecting pathological changes in distinct organ dysfunctions. We measured seven plasma ceramides using liquid chromatography-mass spectrometry (LC-MS) in 1558 patients, including 1262 participants in the retrospective discovery set and 296 patients with WHF in the prospective validation set in BIOMS-HF study (Registry Study of Biomarkers in Heart Failure). Univariate and multivariate logistic regression models were constructed to identify the association between ceramide levels and organ dysfunction. We constructed three ceramide-based scores linked independently to heart, liver, and kidney dysfunction, with ceramides and ratios included in each score specifying systemic inflammation, chronic metabolic disorders, and water-sodium retention. The combined ceramide heart failure score (CHFS) was independently associated with adverse outcomes (Hazard Ratio,2.80[95% CI,1.78-4.40; P<0.001];2.68[95% CI,1.12-6.46; P=0.028]) and improvedthe predictive value of Acute Decompensated Heart Failure National Registry (ADHERE) score and brain natriuretic peptide (BNP; net reclassification index,0.34[95% confidence interval (CI),0.19-0.50];0.42[95% CI,0.13-0.70]) in the discovery and validation set, respectively. Lower BNP levels and higher CHFS were associated with a higher risk of adverse events in patients with WHF. Abnormal plasma ceramide levels associated with heart and peripheral organ dysfunction provide incremental prognostic information regarding the ADHERE score and BNP concentration for risk stratification in patients with WHF. This may facilitate the reclassification of high-risk patients requiring aggressive therapeutic intervention.